Pelaksanaan Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam di SMP Negeri 1 Karanganyar - Kaloko, Naik Saputra (YASIN, 2025)
The limited in-depth research on the implementation of the Kurikulum Merdeka in Islamic Religious Education (Pendidikan Agama Islam, or PAI) serves as the background for this study, given the significant impact of this issue on the quality of learning and character formation among lower secondary school students. The objective of this research is to examine the implementation of the Kurikulum Merdeka in PAI instruction, identify its supporting and inhibiting factors, and explore teachers’ and students’ perspectives on the curriculum at SMP Negeri 1 Karanganyar. This study employs a qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis, using a thematic analysis framework. The findings reveal that the implementation of the Kurikulum Merdeka in PAI has undergone notable adaptation, particularly through the application of differentiated instruction and the execution of Profil Pelajar Pancasila (P5) reinforcement projects. These findings align with constructivist principles and student-centered learning. The study concludes that teacher readiness, school principal support, and the availability of learning resources are key factors determining the successful implementation of the curriculum. The implications include theoretical contributions to curriculum literature in religious education, as well as practical recommendations for the Ministry of Education and schools to enhance PAI teacher training and provide adequate supporting facilities. The study also opens avenues for further research on the long-term effects of the Kurikulum Merdeka on students’ academic achievement and the development of religious character.